Reconociendo mis preferencias - Quezada Guerrero, Jessenia Mercedes (2019)
The bases for the human being's future personality dial the six tender age of life, for it it is necessary than he familiar and school surroundings make a toast the necessary conditions for the development of stocks centered in his comprehensive formation._x000D_ In the initial level specifically at the classrooms of 3 years different areas develop and one of them is the personal social area with his competition construction of his identity that lays stress on development and consolidation of the auto-concept and self-esteem through activities delimited in their needs, interests and preferences._x000D_ He present work makes emphasis in the competition construction of the identity that develops through significant, challenging activities and that they develop the critical thought departing of their needs and interests._x000D_ He present work of professional sufficiency came true with the aim of that the boys and girls of the age of 3 years express their preferences and that they strengthen their decisions departing from a simple game but very significant